2018
DOI: 10.4183/aeb.2018.105
|View full text |Cite
|
Sign up to set email alerts
|

Fat Distribution and Metabolic Profile in Subjects with Hashimoto’s Thyroiditis

Abstract: Context. Previous studies have associated overt/ subclinical hypothyroidism and obesity but have failed to confirm a causative relationship between them. Confusion is even more for subjects with Hashimoto's Thyroiditis (HT).Objective. In this study, we aimed to evaluate the fat distribution and metabolic profile of subjects with euthyroid HT as well as to establish an appropriate cut-off level of TSH for the development of metabolic syndrome (Mets) in both groups.Patients and Methods. All subjects were euthyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 25 publications
0
17
1
Order By: Relevance
“…It is important to note that previous studies in the literature have detected several issues regarding the significant positive correlation between HOMA-IR and blood TSH levels [39][40][41][42][43] and positive correlations with FT4 [42,44,45] and FT3 [42,[45][46][47]. Other studies reported completely opposite results, such as a negative correlation between TSH [44], FT4 [41], FT3 [48], and HOMA-IR.…”
Section: Discussionmentioning
confidence: 89%
“…It is important to note that previous studies in the literature have detected several issues regarding the significant positive correlation between HOMA-IR and blood TSH levels [39][40][41][42][43] and positive correlations with FT4 [42,44,45] and FT3 [42,[45][46][47]. Other studies reported completely opposite results, such as a negative correlation between TSH [44], FT4 [41], FT3 [48], and HOMA-IR.…”
Section: Discussionmentioning
confidence: 89%
“…Mousa et al included 99 Hashimoto's thyroiditis patients with thyroid functions within the normal ranges and 202 healthy volunteers and matched the two groups according to sex, age, BMI, smoking habits, coexistence of thyroid nodules, and menopausal status of female participants. There was no significant difference in NC levels between the thyroiditis group and the control group 24 . A cross‐sectional study of 11,224 euthyroid subjects in Brazil showed that, in both univariate and multivariate models (adjusted for age, sex, race, education, TPOAb, diabetes, cardiovascular disease, glomerular filtration rate and lifestyle behaviours), TSH levels were significantly and positively correlated with BMI and WC, but the positive correlation with NC was not statistically significant in women 25 .…”
Section: Discussionmentioning
confidence: 70%
“…Neck circumference is a relatively fresh and simple anthropometric index for evaluating obesity, and its relationship with thyroid hormones in euthyroid subjects or SHypo patients has also been reported 22‐25 . Belen et al 22 conducted a study in 51 sex‐matched SHypo patients and 51 healthy subjects and found that NC levels were significantly elevated in the SHypo group compared to those in the healthy control group.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicated that NC was not merely a simple indicator for the upper body fat accumulation and was also found to be associated with diabetic complications and effective in identifying subclinical atherosclerosis and nonalcoholic fatty liver disease screening [20][21][22]. A few studies have compared the NC values of those with subclinical hypothyroidism and euthyroid individuals [23][24][25][26]. Belen et al observed that NC in subclinical hypothyroidism patients was significantly higher than that in gender-matched healthy subjects [23].…”
Section: Discussionmentioning
confidence: 99%